(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article addresses the issue of aggressive behavior in interpersonal relationships among adolescent students. The authors provide an overview of some approaches by domestic and foreign scholars regarding the concept of "bullying." It is defined that bullying is aggressive conscious or unconscious behavior of one child, a group of children, youth, or any adult towards another child or children, expressed in physical and/or psychological cruel treatment and behavior. The characteristic features of bullying manifestations in the school environment are clarified. The main types are described (physical school bullying; psychological school bullying: verbal, social; cyberbullying) and the social-role structure of school bullying: bully – the one who harasses, persecutes, inflicts harm on physical or psychological levels; victim – the child who is persecuted and constantly harmed; bystanders, who can be active (those who support the bully and help him commit harmful actions) and passive (do not intervene in the bullying process but passively observe). Factors contributing to school bullying are identified: a favorable social environment; overload of students and teachers leading to emotional burnout; lack of individual approach in teaching and educating students; lack of harmony in relationships among teachers, creating an emotionally unfavorable climate in the pedagogical team; unpreparedness of teachers for gender education of the younger generation. Measures to prevent cases of school bullying are proposed, namely: cooperation between the educational institution administration, teachers, involving a personality-oriented approach to teaching and upbringing, psychologists in providing professional psychological assistance in school conditions, parents in ensuring the creation of a favorable family environment for the child’s development, and students.